Predicting the intention of distracted pedestrians at road crossings. (August 2022) - O'Dell, Amy L.; Filtness, Ashleigh J.; Morris, Andrew P.
Highlights: TPB was applied to predict pedestrian intention to cross the road while distracted. An online survey was conducted with consideration for different types of distraction. Perceived Behavioural Control (PBC) was the most significant predictive factor of intention to cross while distracted. Crossing type significantly predicted PBC, with marked crossings facilitating PBC. Interventions should target marked crossings, where distraction is more prevalent. Abstract: Despite improvements to road safety, accidents involving pedestrians are still numerous, for example in the UK there were over 20, 000 pedestrian casualties on public roads in 2019. One of the potential causal factors is pedestrian distraction. Therefore, this study aimed to predict pedestrian intention to cross the road under conditions of distraction (using phone maps, talking to another pedestrian, listening to music through headphones), by applying the Theory of Planned Behaviour (TPB) using an online survey. This also involved investigation of the impact of selected traffic characteristics (traffic density, vehicle speed) and crossing type (pelican, zebra, unmarked). The survey consisted of 72 questions and took approximately 15 min to complete. The results (N = 81) revealed that the TPB construct of perceived behavioural control (PBC) was a significant predictor of intention to cross the road while distracted across all scenarios. Furthermore, crossing type was a significant predictor of PBC across all scenarios, with marked crossings facilitating feelings of PBC. Findings suggest that high feelings of PBC, as measured through ease and confidence, are linked with stronger intention to cross the road while distracted. This understanding of pedestrian motivation can be used to help design interventions (such as auditory and visual pedestrian warnings) that prevent conflict between distracted pedestrians and vehicles. These interventions should target marked crossing types, whereby pedestrians are more likely to cross while distracted.